Organizational agility: ill-defined and somewhat confusing? A systematic literature review and conceptualization - Anna-Theresa Walter (Management Review Quarterly, 2020)
Superior business performance is a central objective of any firm in an unpredictable environment. Organizational agility (OA) constitutes one option for prospering in this environment. Although research confirms a positive effect of OA on business performance, studies show conceptual imprecision. I systematically review and compile previous findings and provide a coherent view of OA. A search in three databases yielded a final sample of 75 articles. From a qualitative analysis, I identify four agility categories: agility drivers, agility enablers, agility capabilities, and agility dimensions. Based on findings from each category, I develop a conceptual map of OA that (i) connects the agility categories and clarifies how they work, and (ii) proposes a framework for the tasks and responsibilities of management within an agile organization. As part of the conceptualization, I also consider the business environment and the impact of an increased OA level. Viewed from a dynamic capability perspective, changing internal and external agility drivers necessitate the development of agility capabilities. These are realized by a specific set of interdependent enablers. Within this concept of an agile organization, management assumes various responsibilities, in particular, engaging in monitoring and decision-making functions. Conceptual clarity of OA at the organizational level facilitates a systematic development of agility research and provides guidance for practitioners. This article contributes to agility research by integrating insights from various research streams on OA. By highlighting the close ties to strategic management and the derivation of a model to agile management, this research also contributes to strategic management research.
Keywords: L20; 650; Organizational agility; Business performance; Strategic management; Agile management; Systematic literature review